2000
DOI: 10.1093/ptj/80.8.782
|View full text |Cite
|
Sign up to set email alerts
|

Submaximal Exercise Testing: Clinical Application and Interpretation

Abstract: Compared with maximal exercise testing, submaximal exercise testing appears to have greater applicability to physical therapists in their role as clinical exercise specialists. This review contrasts maximal and submaximal exercise testing. Two major categories of submaximal tests (ie, predictive and performance tests) and their relative merits are described. Predictive tests are submaximal tests that are used to predict maximal aerobic capacity. Performance tests involve measuring the responses to standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
304
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(316 citation statements)
references
References 74 publications
3
304
1
8
Order By: Relevance
“…We performed a unique study that objectively investigated different 47 To date, one other survivors' study assessed submaximal endurance using the 6 MWT and found no difference in scores between a group of 49 survivors of NBL and WT versus controls. 22 Our study seems to support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a unique study that objectively investigated different 47 To date, one other survivors' study assessed submaximal endurance using the 6 MWT and found no difference in scores between a group of 49 survivors of NBL and WT versus controls. 22 Our study seems to support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Submaximal exercise testing has been reported as a safe, simple, and well‐tolerated estimate of V O 2max and functional ability in children with chronic disease (20, 22–25). Giannini and Protas (24) showed that children with arthritis had higher submaximal HR and trended towards higher V O 2submax than healthy peers, suggesting significantly lower submaximal efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, V O 2peak may be an inappropriate outcome measure in groups with significant limitations. Instead, submaximal VO 2 (V O 2submax ) may be used as a predictor of V O 2max or as an independent measure of performance in standardized activities (18, 20–23). Giannini and Protas (24) reported that children with JIA had higher submaximal heart rate (HR) and tended towards higher V O 2submax (higher oxygen requirement) as compared with matched controls during a bicycle task.…”
Section: Introductionmentioning
confidence: 99%
“…3 Physical fitness is typically expressed as cardiorespiratory fitness (CRF) and is assessed by exercise tolerance testing. 4 cardiac and respiratory functioning. Directly measured VO 2 max, an objective and quantitative measure of CRF, is a gold standard for assessing the amount of oxygen consumption during exercise testing.…”
Section: Introductionmentioning
confidence: 99%